2018
DOI: 10.1007/s12024-018-0007-6
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal obstruction as a cause of death in the mentally disabled

Abstract: Two cases of intestinal obstruction in the mentally disabled are reported. The first case concerns 61-year-old oligophrenic woman who resided in a nursing home, where she was found hypotensive and unresponsive. Upon opening the peritoneal cavity at autopsy, extremely dilated (measuring on average 12 cm in diameter) loops of the colon emerged- they compressed the small intestine and other intraperitoneal organs, lifting both hemidiaphragms deep into the pleural cavity. Lodged firmly into the rectum, a partly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…For early diagnosis and treatment, caregivers should be trained to recognize signs of distress in their charges, seek immediate medical care, and not hesitate to consult a physician when in doubt. It is also important that medical staff watch for symptoms and signs by performing a careful physical examination especially because these signs and symptoms may be more subtle or less recognizable in patients with MID than in other patients [ 5 ]. In our study, the postoperative complication rate was 28.6%, and the in-hospital mortality rate was 5.7%.…”
Section: Discussionmentioning
confidence: 99%
“…For early diagnosis and treatment, caregivers should be trained to recognize signs of distress in their charges, seek immediate medical care, and not hesitate to consult a physician when in doubt. It is also important that medical staff watch for symptoms and signs by performing a careful physical examination especially because these signs and symptoms may be more subtle or less recognizable in patients with MID than in other patients [ 5 ]. In our study, the postoperative complication rate was 28.6%, and the in-hospital mortality rate was 5.7%.…”
Section: Discussionmentioning
confidence: 99%
“…In another, a young man showing unusual behaviour for several days, possibly experiencing discomfort and pain, and unable to communicate this distress to others, died from constipation complications. 26 A further two cases describe sudden death in two women, one with ASC and one with an LD. 27 Both suffered from chronic constipation.…”
Section: Mortality In Ld And/or Asc Populations Due To Constipationmentioning
confidence: 99%
“…Also, it has been observed that a higher frequency of convulsions in persons with epilepsy may be related to constipation ( Bragg et al., 1994 ). In fact, constipation can be a serious problem resulting in fatal intestinal obstruction due to missed clinical symptoms ( Jancar and Speller, 1994 ; Patja et al., 2001 ), and these may cause death among individuals with severe or profound intellectual disabilities ( Cvetković et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%